Yes-associated protein and immunosuppressive microenvironment in pancreatic cancer development: a new strategy to improve immunotherapy efficacy? - Berardi, Rossana; Bittoni, Alessandro (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Despite extensive research efforts and recent advances achieved in chemotherapy treatment of metastatic disease, pancreatic ductal adenocarcinoma (PDAC) prognosis remains dismal and it has been estimated that PDAC deaths will be second only to lung cancer by 2020 in United States (1). Therefore new therapeutic strategies are urgently needed.